2019
DOI: 10.1016/j.jor.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Microporous polysaccharide hemosphere efficacy and safety in primary total knee arthroplasty

Abstract: Absorbable hemostats such as microporous polysaccharide hemospheres (MPH) are used to manage hemostasis and prevent complications in total knee arthroplasty (TKA). We aimed to determine safety and effectiveness of MPH use in TKA. Records were reviewed for blood loss, hematomas, and infections. No differences existed regarding demographics, superficial infections (P = 0.933) or hematomas (P = 0.393). Positive correlation existed between hematoma and superficial infection (P = 0.009). Blood loss was greater in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…MPH is theoretically expected to reduce hemorrhage and serous exudate ( 1 , 3 ), while its clinical effectiveness remains controversial. Several randomized, controlled studies in various types of surgery, including breast surgery, could not establish the effectiveness of MPH ( 4 - 6 ), while other retrospective studies showed the effectiveness of MPH in cardiothoracic surgery and total knee arthroplasty ( 7 , 8 ). One reason for such a discrepancy may be the small study populations that were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MPH is theoretically expected to reduce hemorrhage and serous exudate ( 1 , 3 ), while its clinical effectiveness remains controversial. Several randomized, controlled studies in various types of surgery, including breast surgery, could not establish the effectiveness of MPH ( 4 - 6 ), while other retrospective studies showed the effectiveness of MPH in cardiothoracic surgery and total knee arthroplasty ( 7 , 8 ). One reason for such a discrepancy may be the small study populations that were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized, controlled studies could not demonstrate the effectiveness of MPH in patients who underwent breast, thyroid and endoscopic sinus surgery ( 4 - 6 ). In contrast, the effectiveness of MPH in cardiothoracic surgery and total knee arthroplasty has been shown in several retrospective analyses ( 7 , 8 ). In this retrospective study, we evaluated the effectiveness of MPH in breast cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…MPHs use a sophisticated polymer crosslinking process based on plants to produce ultrahydrophilic, biocompatible particles. By absorbing the liquid portion of the blood and increasing the concentration of platelets and coagulation factors, they aid in the coagulation cascade [ 72 ]. Regardless of the patient’s coagulation status, the clotting process begins upon contact.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, bandages with MPH applied to skin defects from Mohs surgery actually increased bleeding through the bandage and did not significantly affect bleeding after bandage removal 27 . MPH may similarly worsen bleeding after total knee arthroplasty 28 and in one animal study, it resulted in an increased risk of distal tip necrosis of local skin flaps 29 . In light of this, MPH should be used cautiously in areas undergoing locoregional reconstruction or within free flap recipients sites.…”
Section: Discussionmentioning
confidence: 99%